RANCANG BANGUN SISTEM INFORMASI PENERIMAAN PESERTA DIDIK BARU ONLINE PADA SEKOLAH DASAR MUHAMMADIYAH MERUYUNG BERBASIS WEB - Alta Gilbran Ardana (2022)
Admission of prospective new students is a process that occurs every year in every school to screen new students who meet school criteria, one of which is SD Muhammadiyah Meruyung. In the process of accepting new students, SD Muhammadiyah Meruyung still uses conventional methods, namely brochures and paper forms. This conventional method allows for data loss and also takes time when inputting forms. From these problems, an information system for new student admissions is needed that can reduce the obstacles that occur in the conventional admissions process. In this new system, starting from registration information, filling out forms, checking data, and reporting on the results of the selection will be in the form of a website. The design of this website uses the waterfall method and the PHP programming language. It is hoped that this new system will simplify and assist the process of admitting new students at SD Muhammadiyah Meruyung.